Pengaruh Insentif Pajak pada Hubungan antara Digitalisasi, Sosialisasi, Kompleksitas dan Kepatuhan Wajib Pajak - Purnama Dewi, Ni Made Resita; Wirakusuma, Made Gede; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
The research objective is to determine the effect of digitizing tax services, tax socialization and tax complexity on taxpayer compliance with tax incentives as a moderating variable. The number of samples obtained was 384 respondents using the proportional stratified sampling technique. Data collection was carried out using a questionnaire survey method. The data analysis technique used is Partial Least Square (PLS). Based on the research results, digitization of tax services, tax complexity and tax incentives have a positive effect on individual taxpayer compliance for Micro, Small & Medium Enterprises (MSMEs), but tax socialization has no significant effect on individual taxpayer compliance for MSME actors. Tax incentives weaken the effect of digitizing tax services on individual taxpayer compliance of MSME actors. Tax incentives strengthen the effect of tax socialization on individual taxpayer compliance of MSME actors. Tax incentives have not been able to play a role as a variable moderating the effect of tax complexity on individual taxpayer compliance of MSME actors. Keywords: Digitalization Of Tax Services; Tax Socialization; Tax Complexity; Individual Taxpayer Compliance Of MSME, Tax Incentives